2018
DOI: 10.1101/277517
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of strain level diversity on robust inference of virus-induced mortality

Abstract: Infection and lysis of phytoplankton by viruses affects population dynamics and nutrient cycles within oceanic microbial communities. However, estimating the quantitative rates of viral-induced lysis remains challenging in situ. The modified dilution method is the most commonly utilised empirical approach to estimate virus-induced killing rates of phytoplankton. The lysis rate estimates of the modified dilution method are based on models of virus-host interactions involving only a single virus and a single hos… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The dilution effect probably explains links between host communities and transmission. In their model of virus infection of plankton based on life-history traits, Beckett and Weitz (2018) found that lysis rates were driven by the strains with the fastest replication and not those with the greatest abundance.…”
Section: 2trait-based Models Focusing On Planktonmentioning
confidence: 99%
“…The dilution effect probably explains links between host communities and transmission. In their model of virus infection of plankton based on life-history traits, Beckett and Weitz (2018) found that lysis rates were driven by the strains with the fastest replication and not those with the greatest abundance.…”
Section: 2trait-based Models Focusing On Planktonmentioning
confidence: 99%